"Conversion Therapy" Experiences in Their Social Contexts: A Qualitative Study of Sexual Orientation and Gender Identity and Expression Change Efforts in Canada. (June 2022) - Kinitz, David J.; Goodyear, Trevor; Dromer, Elisabeth; Gesink, Dionne; Ferlatte, Olivier; Knight, Rod; Salway, Travis
Objective: To describe in what forms, with whom, where, when, and why Canadians experience sexual orientation and gender identity and expression change efforts (SOGIECE). Methods: This qualitative study is grounded in a transformative paradigm. We conducted semi-structured interviews with a purposive sample of 22 adults recruited from across Canada who have experienced "conversion therapy." Directed content analysis was used, employing deductive and inductive coding approaches, to synthesize the findings and address 5 policy-relevant questions. Results: What are SOGIECE? Formal and informal methods of SOGIECE were used, including pharmacologic interventions, denial of gender-affirming care, and coaching to repress sexual orientation and/or gender identity and expression. With whom did SOGIECE occur? Practitioners included religious leaders, licenced health-care professionals (e.g., psychiatrists and psychologists), peers, and family members. Where did SOGIECE occur? SOGIECE occurred in 3 predominant settings: faith-based, health care, and social life. When did SOGIECE occur? SOGIECE rarely occurred over a restricted time frame; often, SOGIECE began while participants were adolescents or young adults and continued multiple years under various forms. Others described SOGIECE as a context in which their life was embedded for many years. Why did people attend SOGIECE? Cisheteronormative social and religious expectations taught participants that being non-cisgender or non-heterosexual was incompatible with living a good and respectable life. Conclusions: SOGIECE are not a circumscribed set of practices. Our study shows that SOGIECE are a larger phenomenon that consists of intentional and explicit change efforts as well as heterosexual- and cisgender-dominant social norms expressed and enforced across a wide range of settings and circumstances. This study provides critical context to inform contemporary social and health policy responses to SOGIECE. Policies should account for the overt, covert, and insidious ways that SOGIECE operate in order to effectively promote safety, equity, and health for sexually diverse and gender-diverse people.